2021
DOI: 10.1037/edu0000602
|View full text |Cite
|
Sign up to set email alerts
|

Math anxiety interferes with learning novel mathematics contents in early elementary school.

Abstract: conceived the study, modeled and analyzed the data, and wrote the first and successive drafts of the manuscript. Veronica Guardabassi and Patrick A. O'Connor aided with the study design and the development of training materials, collected all data, performed data analysis, and contributed to the revision of the manuscript drafts. All authors made a substantial intellectual contribution to this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 72 publications
1
16
0
1
Order By: Relevance
“…Based on these two theories, it is not surprising that OTL showed direct effects on student problem-solving performance and mathematics performance, as well as indirect effects mediated by mathematics anxiety in the current study. Although limited empirical research has explored the direct and indirect effects of instructional quality on student mathematics performance through mathematics anxiety, a large amount of research confirmed the positive effects of qualified mathematics content on student mathematics-related cognitive skills and mathematics performance (Cogan et al, 2001;Byrnes and Miller, 2007;Lleras, 2008;Byrnes and Wasik, 2009;Lee and Chen, 2009;Reeves, 2012;Albano and Rodriguez, 2013;Grouws et al, 2013;Tar et al, 2013;Ottmar et al, 2014;Schmidt et al, 2015;Santibanez and Fagioli, 2016), as well as the studies on training or tutoring programs provided some evidence for the effects of mathematics content and skills on student mathematics anxiety (Frenzel et al, 2007;Supekar et al, 2015;Ching et al, 2020;Passolunghi et al, 2020;Tomasetto et al, 2021). When students get better content coverage on the key topics in their daily mathematics lessons, they may feel less anxious about mathematics and they may be capable to use proper cognitive skills or strategies to solve complex problems, and all of these may lead to a better mathematics performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these two theories, it is not surprising that OTL showed direct effects on student problem-solving performance and mathematics performance, as well as indirect effects mediated by mathematics anxiety in the current study. Although limited empirical research has explored the direct and indirect effects of instructional quality on student mathematics performance through mathematics anxiety, a large amount of research confirmed the positive effects of qualified mathematics content on student mathematics-related cognitive skills and mathematics performance (Cogan et al, 2001;Byrnes and Miller, 2007;Lleras, 2008;Byrnes and Wasik, 2009;Lee and Chen, 2009;Reeves, 2012;Albano and Rodriguez, 2013;Grouws et al, 2013;Tar et al, 2013;Ottmar et al, 2014;Schmidt et al, 2015;Santibanez and Fagioli, 2016), as well as the studies on training or tutoring programs provided some evidence for the effects of mathematics content and skills on student mathematics anxiety (Frenzel et al, 2007;Supekar et al, 2015;Ching et al, 2020;Passolunghi et al, 2020;Tomasetto et al, 2021). When students get better content coverage on the key topics in their daily mathematics lessons, they may feel less anxious about mathematics and they may be capable to use proper cognitive skills or strategies to solve complex problems, and all of these may lead to a better mathematics performance.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the poorer knowledge in quantitative reasoning and number students have, the more anxious they may feel in mathematics-related activities. Tomasetto et al (2021) also showed student mathematics anxiety was negatively related to their initial level of mathematics knowledge. It is the content coverage in school daily instruction from which most students mainly learn mathematics.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Conversely, students in western countries such as Finland, the Netherlands, and Liechtenstein, tended to have high mathematics self-efficacy and mathematics self-concept and low mathematics anxiety, yet had high mathematical performance. Mathematics anxiety has often been negatively associated with mathematical achievement (e.g., Tomasetto, 2020), but some studies have found a positive association between them (e.g., Hunt et al, 2017). These results suggest that mathematics self-efficacy and selfconcept may be differentially related to mathematical achievement across countries.…”
Section: Student-level Variablesmentioning
confidence: 92%
“…In practice, however, exercises should be fairly distributed in accordance with the amount of content in the textbook and syllabi. Unequal distribution of content and corresponding exercises will not lead to a complete accomplishment of educational objectives or curriculum ends [35].…”
Section: Proportion Of Major Topics and Exercises Of The Textbooksmentioning
confidence: 99%